2021
DOI: 10.1080/17437199.2021.1938632
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health behaviour change during pregnancy: a systematic review and meta-synthesis

Abstract: Pregnancy is an opportune time for women to make healthy changes to their lifestyle, however, many women struggle to do so. Multiple reasons have been posited as to why this may be. This review aimed to synthesise this literature by identifying factors that influence women's health behaviour during pregnancy, specifically in relation to dietary behaviour, physical activity, smoking, and alcohol use. Bibliographic databases (MEDLINE, PsycINFO, CINAHL-P, MIDIRS) were systematically searched to retrieve studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…Hence, this emphasizes critical individual differences in human behaviour and decision-making. Therefore, the delivery of health promotion advices as PCC-messages should be tailored to the individual level and match personal health beliefs while simultaneously acknowledging the barriers women face to act upon health-promoting behaviours [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this emphasizes critical individual differences in human behaviour and decision-making. Therefore, the delivery of health promotion advices as PCC-messages should be tailored to the individual level and match personal health beliefs while simultaneously acknowledging the barriers women face to act upon health-promoting behaviours [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the systematic review and meta-synthesis have been reported in full elsewhere (Rockliffe et al, 2021 ). In brief, four bibliographic databases were searched (MEDLINE, PsycINFO, CINAHL-P, and MIDIRS) on 11/12/18 (and updated on 02/09/20) for studies providing qualitative data about women's experiences or perceptions of behaviour change specific to dietary behaviour, physical activity, smoking, and alcohol use, during an uncomplicated pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Additional records were identified using alternative search methods ( n = 36). Ninety-two studies were included in the review (see Rockliffe et al, 2021 for list of included studies). Study data were extracted using a data extraction tool, and study quality was assessed using a modified version of the Critical Appraisal Skills Programme qualitative appraisal checklist (CASP; Critical Appraisal Skills Programme, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, PA is a particularly important prerequisite for the majority of the aspects of human health, especially the population in the reproductive period, and more specifically, pregnant women [ 4 ]. Pregnant women are particularly fragile and sensitive to external and internal influences, with a special focus on fetal health [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%